(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2014)
The majority of major cities in the world city network are capital cities. Between primacy and political specialization there are examples of countries where the capital city and a second city remain as major rival cities in contemporary globalization. In this paper we focus upon situations where the capital city is less important in global economic capacity: Rome and Milan, Berlin and Frankfurt, Abu Dhabi and Dubai, Delhi and Mumbai, Islamabad and Karachi. This is an exercise in double comparisons: between cities in each pairing and between the pairings. Despite the massive differences – economic, cultural and political – amongst our chosen pairs of cities we have found communalities relating to the specific circumstance we are investigating. First, there is some evidence that economic centres are more global and less local than their capital cities. Second, more particularly, we have shown that in terms of global economic connections there is a very consistent pattern: economic centres have a much more coherent and telling integration into the world city network.